If it's not what You are looking for type in the equation solver your own equation and let us solve it.
b in (-oo:+oo)
60 = (8*(b+3))/2 // - (8*(b+3))/2
60-((8*(b+3))/2) = 0
60-4*(b+3) = 0
60-4*(b+3) = 0
48-4*b = 0
48-4*b = 0
48-4*b = 0 // - 48
-4*b = -48 // : -4
b = -48/(-4)
b = 12
b = 12
| -46=-2x-3x-6 | | 4+4x=16+4x | | -4+3x+6x=41 | | 6x-8y=-4 | | 75=0.2*x | | 2x^2-3x+18=0 | | 5+9i/1+i | | z/3-8=14 | | 56x-14/24x-6 | | x+2x+x=y | | 21/3+r=43/4 | | 4(3a+6)= | | 3(d-5)=15 | | 40+x=2x | | X+3=9+2 | | -5x-9=-14 | | 1/10r=41/2 | | 3x-5x=-10-20 | | 2-x=3x+6 | | (p^2-4p-21)/(p^2-2p-35) | | 2/7r=6 | | X+x=10-2 | | 4x=136+9x | | 9-10x=83-24x | | 31x+21x=21 | | 4x+3x=10+4 | | 10=4*T*20/100 | | -64x^2+104x= | | 4x+x+20=200 | | 4/3r=31/2 | | 28=4-3p | | -43-4=7-9x |